RISK FACTORS OF UNCONTROLLED HYPERTENSION AMONG PEOPLE IN SULAIMANI CITY ACCORDING TO THE HYPERTENSION GUIDELINE OF AHA/ACC 2017 - Karem, Omed Hama; Abdulrahman, Zana Ismael; Ahmad, Farman Jaafar (Journal of Sulaimani Medical College, 2020)
Background Hypertension is the major risk factor for cardiovascular disease (CVD) morbidity and mortality globally, which accounts for nearly half of the CVD events. A striking change has happened in the diagnosis of hypertension and its management after the introduction of the 2017 hypertension guideline by the American College of Cardiology and American Heart Association (ACC/AHA). Objectives To detect risk factors of uncontrolled hypertension according to ACC/AHA 2017 Guideline. Patients and Methods A cross-sectional study conducted at Ali Kamal outpatient clinic, a total of 282 uncontrolled hypertensive patients were collected and evaluated for risk factors of uncontrolled hypertension, including gender, age, body mass index & other variables. Results A total of 282 patients were included in this study.The mean ± SD age was 55.4 ± 12.5 (ranged from 30 to 84) years and around 68.4 % (n= 193) were females. A high percentage of 77.3% were living in rented houses. Their mean BMI was 28.4 ± 4 kg/m2 (ranged from 19.5 to 51.9). Minority of participants.13.5% (n=38), had normal body mass index, 49.6% (n=140) were on triple antihypertensive therapy. The duration of hypertension was less than 10 years in 45 % (n=127).48% (n=136) of the patients were taking the medications from mixed sources (governmental and private sector). The mean DBP of the patients was 87.7±8.4 mm Hg, while the mean SBP was 147±15.4 mmHg and 96.5% (n=272) of the patients were adherent to the medications. Conclusion Hypertension is a major risk factor for CAD; every patient with uncontrolled hypertension must be evaluated for any associated comorbidity, and strongly advised against smoking and obesity especially with advanced age.
Keywords: Uncontrolled hypertension; Risk factors; Non-adherence